Effect of Preoperative Lactobacillus acidophilus Supplementation on Postoperative Gastric Residual Volume after Lower Digestive Laparotomy: A Randomized, Double-Blind, Controlled Trial - Christophorus Simadibrata Christophorus; Rudyanto Sedono Rudyanto; Sidharta Kusuma Manggala Sidharta Kusuma; Wifanto Saditya Jeo Wifanto Saditya (Frontiers on Healthcare Research, 2026)
Background: Gastrointestinal dysmotility is among the most common complications after abdominal surgery and is reflected clinically by an elevated gastric residual volume (GRV), which increases the risk of aspiration and delays enteral feeding. Lactobacillus acidophilus is thought to improve gut motility through luminal acidification, competitive exclusion of pathogens, and direct stimulation of smooth-muscle contractility, but whether this translates into a lower GRV after digestive laparotomy has not been tested. Objective: To determine whether preoperative Lactobacillus acidophilus supplementation reduces postoperative GRV after lower digestive laparotomy. Methods: In this randomized, double-blind, placebo-controlled trial at Dr. Cipto Mangunkusumo National General Hospital, Indonesia, adults scheduled for elective laparotomy of the jejunum, ileum, colon, or rectum received oral Lactobacillus acidophilus 10⁹ CFU or an identical placebo capsule three times daily for three days before surgery. A nasogastric tube inserted during surgery was aspirated every 6 hours after ICU admission; GRV was categorized as normal (<250 mL/24h) or increased (≥250 mL/24h) at 24 and 48 hours. Results: Fifty-five participants were randomized (27 probiotic, 28 placebo); one placebo-group participant was withdrawn because of sepsis, leaving 54 participants analyzed per protocol. GRV was increased in 4/27 (14.8%) probiotic recipients versus 2/27 (7.4%) placebo recipients at 24 hours (p = 0.669; risk ratio for normal GRV 0.92, 95% CI 0.76–1.11) and in 1/27 versus 0/27 at 48 hours (p = 1.000). Stratified analysis identified age, neurological comorbidity, obesity, vasopressor use, opioid exposure, hypercapnia, and hyperglycemia as confounders that shifted the crude risk estimate by more than 10%; opioid and vasopressor exposure were also unevenly distributed between groups at baseline (p = 0.006 and p = 0.026, respectively). Conclusion: A 3-day preoperative course of Lactobacillus acidophilus did not significantly reduce postoperative GRV after lower digestive laparotomy. The trial was underpowered relative to its planned sample size, and an uneven distribution of opioid and vasopressor exposure between groups may have obscured a true effect.